PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH WANKAT DAN OREOVOCZ TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMKN 1 PULAU PUNJUNG TAHUN PELAJARAN 2012/2013 - Haverdi, Jefri; Zulfaneti, Zulfaneti; Yunita, Alfi (Pendidikan Matematika, 2013)
Based on background knowledge of this research was studentsâ ability in solvingÂ  mathematical problem that still low, one way to solve this problem was applied problem solving strategy Wankat and Oreovocz. The purpose of this research was to know 1) whether studentsâ ability to solve the problem by using problem solving strategy Wankat and Oreovocz better than conventional strategy, 2) how the students attitude through learning activities by using problem solving strategy Wankat and Oreovocz. Type of this research was experiment. Population of this research was students at X Grade of SMK N 1 Pulau Punjung. In choosing sample used randomly technique.Â  X TKJ 2 as experimental class and X TKJ 1 as control class. Ability of problem solving test and questionaire as instrumentation in this research with r11= 0.73. Data analysis was done by using Mann Withney test through MINITAB Sofware. From the data analysis get Â with P-value = 0.0076. So, we can conclude that studentsâ ability in problem solving of mathematical concept by using Wankat and Oreovocz better than conventional strategy at X Grade of SMK N 1 Pulau Punjung, based on questionare, studentsâ attitude in learning activities by using problem solving strategy Wankat and Oreovocz was better.